EFEKTIVITAS PROSES PENGOMPOSAN SAMPAH DAUN DENGAN TIGA SUMBER AKTIVATOR BERBEDA - Widiyaningrum, Priyantini; Lisdiana, Lisdiana (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
The purpose of this study was to evaluate the effectivity of the leaf garbage composting process were given three different kinds of activators.The material composed are chopped leaf garbage and goat manure in the ratio of 3: 2, and make in three activators treatments. There are activators of orange peel waste, vegetable waste and EM4 product as a comparison. Compost is harvested after the composting process lasted for 21 days. The variables measured include (1) changes in daily temperature, pH, humidity compost during the composting process, (2) quality parameters such as physical parameters (texture, colour, odor, and depreciation), and chemical parameters (water content, pH, and C/N ratio). All of data were analyzed descriptively. The changes of daily temperature, pH, and humidity on EM4 compost activator treatment showed highest depreciation (39.3%) followed by compost with vegetable Mol and waste orange peel ( 31.6% and 29.8%), while the graphs of pH and humidity appear constant during this process. Accordance with the percentage of the depreciation, C/N ratio of the compost with EM4 activator showed the lowest (14.73). Generally, parameters of texture, colour and odor no different, as well as the water content and pH. This study concludes that composting treatment successfully and produce compost according to the criteria of SNI standard Number 19-7030-2004.